2019
DOI: 10.1186/s13765-019-0408-6
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and thermal properties of Pistacia atlantica subsp. Kurdica gum

Abstract: Pistacia atlantica subsp. Kurdica (PAK) is distributed throughout the Zagros Mountains and is indigenous to Kurdistan province in western Iran. This study focused on the composition and thermal properties of gum extracted from female and male trees from six regions of Kurdistan province. Significant differences were detected in the total protein, total ash, total carbohydrate and monosaccharaide contents according to gender and geographic region, but no significant difference was found for moisture content. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 43 publications
(48 reference statements)
2
17
0
Order By: Relevance
“…The most abundant monosaccharides were arabinose (30.30%), galactose (18.2%), and galacturonic acid (17.69%). Our nding was in agreement with similar research by Mirahmadi et al [21].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The most abundant monosaccharides were arabinose (30.30%), galactose (18.2%), and galacturonic acid (17.69%). Our nding was in agreement with similar research by Mirahmadi et al [21].…”
Section: Resultssupporting
confidence: 94%
“…Mirahmadi et al [21], and Salimi et al [29] who indicated that α-Pinene is the main compound in the ethanolic extract of Bene gum. α-Pinene is a highly bioavailable component with rapid metabolism and exhibits activity as an acetylcholinesterase inhibitor [30] and positive modulator of GABAAbenzodiazepine (BZD) receptors [31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than five distinct absorption peaks are observed (Figure . 6); This confirms the complex nature of the studied samples (41). The broad and strong peak observed between 3000-3700 cm -1 is du to the stretching vibration of the hydroxyl (-OH) group of of alcoholic and phenolic compounds, and stretching vibration of the amine (-NH) group (42,43). The peaks at 2920 and 2842 cm -1 are attributed to the asymmetric and symmetric stretching of the methylene (CH2) and methyl (CH3) groups (44,45), and the peak corresponding to stretching vibrations -NH2 + , -NH + , and -NH groups appears in the range 2300-2800 cm -1 usually (46).…”
Section: Fourier Transform Infrared (Ft-ir) Spectroscopy Of Pa-lpsupporting
confidence: 73%
“…The peaks at 2920 and 2842 cm -1 are attributed to the asymmetric and symmetric stretching of the methylene (CH2) and methyl (CH3) groups (44,45), and the peak corresponding to stretching vibrations -NH2 + , -NH + , and -NH groups appears in the range 2300-2800 cm -1 usually (46). The observed peak at 1700-1725 cm -1 is attributed to stretching of carbonyl (C=O) group of carboxylic acid or ketones (43,47), and the peak at 1620 cm -1 appears for C=O bond stretch of the amide group, or N-H bond bend, or carbonyl group stretch of -COOH (41,44,48). The peak 1536 cm -1 belongs to carboxyl groups (44), and the peak 1454 cm -1 corresponds to the bending of C-H group that appears in the range 1445-1485 cm -1 (41), and the peak 1370 cm -1 is attributed to the bending of CH3 group or C-N stretching vibration, which corresponds to the amine groups (8,47,49).…”
Section: Fourier Transform Infrared (Ft-ir) Spectroscopy Of Pa-lpmentioning
confidence: 99%